Corrosion Fatigue Analysis in Power Steam Turbine Blade - José Alfredo Rodrígez Ramírez; Christian Marisol Clemente Mirafuentes; Manuela Alejandra Zalapa Garibay; Juan C. García Castrejón; Luis Gonzalo Guillén Anaya (Metals, 2023)
The corrosion fatigue behavior of a martensitic stainless steel AISI 410 with 12% Cr, used in the fabrication of steam turbine blades at low pressure (L-P), was studied using the electrochemical noise technique (EN) under mechanical fatigue (immersion and aired) conditions. The tests were done in a simulated environment using four levels of mechanical stress (Δσ) in a 3 wt.% NaCl solution at 90 °C. The specimens underwent pitting corrosion when exposed to the corrosive environment; afterwards, such pits generated mechanical strength sites over the metallic surface, facilitating the initiation and propagation of cracks, which was already enhanced by the applied cyclic loads. From scanning electron microscope (SEM) images, it was possible to observe localized plastic deformation. In such instances, the fatigue damage was caused by the microplasticity (μ), i.e., the shear strength, resulting from the breakdown of the passive layer that was subjected to mechanical load, which led to a significant increment of the velocity of crack propagation, and therefore, a decrement of the useful life of the material. The obtained results show that the fatigue resistance limit in the corrosive medium was lower than that observed in aerated conditions due to the sum of the effects of mechanical fatigue and corrosion.